Point source calibration of the AKARI/FIS all-sky survey maps for stacking analysis. (16th April 2014) - Arimatsu, Ko; Doi, Yasuo; Wada, Takehiko; Takita, Satoshi; Kawada, Mitsunobu; Matsuura, Shuji; Ootsubo, Takafumi; Kataza, Hirokazu
Abstract : Investigations of the point spread functions (PSFs) and flux calibrations for stacking analysis have been performed with the far-infrared (wavelength range of 60 to 140 μm) all-sky maps taken by the Far-Infrared Surveyor (FIS) on board the AKARI satellite. The PSFs are investigated by stacking the maps at the positions of standard stars with their fluxes of 0.02–10 Jy. The derived full widths at the half maximum (FWHMs) of the PSFs are ∼ 60 ′ ′ at 65 and 90 μm and ∼ 90 ′ ′ at 140 μm, which are much smaller than those of the previous all-sky maps obtained with the Infrared Astronomical Satellite IRAS (∼ 6 ′ ). Any flux dependence in the PSFs is not seen on the investigated flux range. By performing the flux calibrations, we found that absolute photometry for faint sources can be carried out with constant calibration factors, which range from 0.6 to 0.8. After applying the calibration factors, the photometric accuracies for the stacked sources in the 65, 90, and 140 μm bands are 9%, 3%, and 21%, respectively, even below the detection limits of the survey. No systematic dependence between the observed flux and model flux is found. These results indicate that the FIS map is a useful dataset for the stacking analyses of faint sources at far-infrared wavelengths.